The hisP Protein, a Known Histidine Transport Component in Salmonella typhimurium, Is Also an Arginine Transport Component - Kustu, Sydney Govons (1973)
The hisP protein is an essential component of the high-affinity histidine transport system in Salmonella typhimurium. Our present studies demonstrate that this protein is also an essential component of an arginine transport system. Strains with a mutation in the hisP gene are unable to transport arginine for use as a sole nitrogen source. However, such strains have normal high-affinity transport of arginine, indicating that the hisP protein is not required for all arginine transport systems. Histidine does not appear to compete with arginine for transport through the hisP system, suggesting that the hisP protein may not be a “carrier” for these amino acids. The hisJ protein, a periplasmic histidine-binding protein, is known to function in conjunction with the hisP protein in the transport of histidine. The hisJ protein does not function with the hisP protein in arginine transport.